Optimising delivery of integrated palliative care and heart failure services: A realist evaluation protocol (PalliatHeartSynthesis II) - Tracey McConnell; David Scott; Geoffrey Wong; Loreena Hill; Miriam J. Johnson; Yvonne Millerick; Joy Ross; Clea Atkinson; Linda Cooper; John Burden; Rachel Campbell; Andrew Kerr; et al. (PLoS ONE, 2026)
Background Inequality in palliative care provision is an ongoing problem for underserved groups, such as those with heart failure (HF) placing a burden on patients, their caregivers and health services due to frequent, often avoidable hospitalisations. Our realist synthesis of integrated palliative care (PC) and HF literature found that integrated HF and PC services work best when service providers are motivated and have the opportunity and capacity to support behaviour change. However, we identified significant knowledge gaps with most studies completed in United States of America (USA) and based primarily on the views of nurses and physicians. We developed strategies to help services provide integrated PC and HF services but identified the need for United Kingdom (UK) primary data to better understand the context-specific implementation of palliative care and HF care. Methods This project will use co-design and realist evaluation to generate data from five PC and HF integrated services in the UK, purposively sampled to provide variation in geography and service design (Research Registry 10624). The research comprises three work packages (WPs). WP1 will deliver a realist evaluation of each site including documentary analysis, observations and semi-structured interviews with service providers and users. WP2 uses co-design methods to develop a guide to help others set up and improve integrated PC and HF services. Data from both WPs will be analysed and synthesised using a realist logic of analysis. WP3 will facilitate the development of a community of practice to support those who wish to set up, sustain and embed integrated PC and HF services. Discussion This realist evaluation of a complex intervention will improve understanding of how to tailor and implement integrated PC and HF services. The co-designed ‘how-to guide’ and community of practice will facilitate knowledge translation and ensure that evidence-based guidance is provided to assist in service development.